Vrednotenje geografskega okolja in okoljska etika - Plut, Dušan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2008)
Changes in the value systems, including the principles of environmental ethics, have to be effectuated in the material life of the society and of individuals, and they also have to exert influence on the apprehension and evaluation of geographical environment. A move must be made forth, away from the mainly anthropocentric apprehension of geographical environment which is no longer merely the scene of economy and the dwelling environment of humans, but it also has the ecosystem, protective significance.
Keywords: ecology; ekologija; environmental protection; varstvo okolja; ekološko ravnotežje; sustainable development; trajnostni razvoj; sonaravni razvoj; vrednote; okoljska etika